Nurses’ roles in palliative care: An Islamic perspective - Edy Suprayitno; Iwan Setiawan (Belitung Raya Foundation, Indonesia, 2021)
Palliative care is an important approach for nurses to improve the quality of life of patients holistically and mitigate suffering among the patients in critical condition and near to death. This article provides an Islamic perspective about nurses’ roles in palliative care, which can be applied worldwide, especially in Muslim-majority countries. Understanding Islamic beliefs will help nurses provide professional and culturally sensitive nursing care. In its principle, Islam always respects the process of life until death comes. So, the application of Islamic values in palliative care will make the patients accept their ill condition completely, keep being close to Allah SWT (God), and die peacefully. The concepts of illness, death, early action on the dead, and palliative care application in nursing are explained in this article to open up new ideas rather than provide definitive answers. We hope that this perspective will highlight healthcare policymakers the need to integrate Islamic values in nursing practice.